A preliminary study evaluating trans-fat content of pastries insocioeconomically disadvantaged communities of Istanbul - (:unkn) unknown (My University, 2021)
Objective: Trans-fatty acids (TFAs) pose several risks to human health. World Health Organization recommends the elimination oftrans-fat consumption through limiting their use as less than 2g/100g fat. In line with this recommendation, Turkey recently passed anew regulation securing the content of TFAs as less than 2g/100g fat in industrially produced foods. The objective of this study was todetermine the proportion of high TFA (>2 g/100g fat) in pastries among socioeconomically disadvantaged communities of Istanbulbefore the regulation was put into force.Materials and Methods: Eight socioeconomically disadvantaged districts were chosen from Istanbul and from each district threeneighborhoods with the lowest land values were identified. Pastry samples were collected from 72 shops. TFA content was analyzedat Scientific and Technological Research Council of Turkey (TUBITAK) Marmara Research Center by the ISO 12966-2:2011 method.p<0.05 was set as the level of statistical significance.Results: The median (25th-75th percentile) value of TFAs was 0.19g/100g (0.04g/100g – 0.30g/100g). None of the samples exceededthe level of 2g/100g. There was no difference in TFA content between the districts (p>0.05).Conclusion: Our findings indicate that Turkey could easily comply with the legislative limit of 2%. Still, the compliance shouldcontinuously be evaluated in diverse populations of the country.